Anti-aging electric wire and cable and preparation process thereof
By using acrylic copolymers, modified titanium dioxide and nano-grade aluminum-magnesium hydrotalcite in the protective layer of wires and cables, combined with the extrusion process, the problem of insufficient aging resistance and mechanical properties of wires and cables is solved, and the problem of significantly improved The aging resistance and mechanical properties of wires and cables extend the service life.
Patent Information
- Application Number
- CN202411294566.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Wires and cables are susceptible to external factors during long-term use, resulting in a decline in aging resistance, increasing the risk of fracture, and insufficient mechanical properties, which is difficult to effectively solve the problem of the existing technology.
Using a protective layer composed of linear high-density polyethylene, acrylate copolymer, modified titanium dioxide and nano-scale aluminum-magnesium hydrotalcite, wires and cables are prepared through the extrusion process, and the surface modification of modified titanium dioxide and ternary polycarboxylic acids is modified. and synergistically, enhancing the bonding power of the protective layer.
It significantly improves the mechanical properties and aging resistance of wires and cables, extends the service life and reduces the risk of fracture.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cables, and in particular to an aging-resistant electric wire and cable and a preparation process thereof. Background Art
[0002] Wires and cables are important infrastructure for power transmission and information transmission, and are widely used in various fields, including power systems, communication systems, transportation systems, construction, industrial automation, etc. In power and communication systems, they are used to transmit and distribute electrical energy and transmit various signals and data; in industrial automation, they are an important part of connecting and controlling equipment. Wires and cables are usually composed of one or more insulated cores, as well as an insulating layer and a protective layer. Among them, the protective layer of wires and cables provides additional physical protection for the cables, and plays a vital role in ensuring the normal operation and extending the service life of wires and cables. However, during the long-term use of wires and cables, they will be affected by various external factors such as rain and light, which will lead to a decrease in their aging resistance and reduce their service life. In addition, when the aging resistance of wires and cables decreases, their mechanical properties will also decrease, thereby increasing the risk of breakage during operation. Therefore, improving the mechanical properties and aging resistance of wires and cables is a technical problem that needs to be solved urgently. Summary of the invention
[0003] The invention provides an aging-resistant electric wire and cable and a preparation process thereof, which solves the problems of poor mechanical properties and poor aging-resistant properties of the electric wire and cable in the related art.
[0004] The technical solution of the present invention is as follows: The present invention provides an aging-resistant electric wire and cable, which comprises a conductor, an insulating layer and a protective layer from the inside to the outside, and the protective layer comprises the following components in parts by weight: 70 parts of linear high-density polyethylene, 20-30 parts of acrylic copolymer, 15-35 parts of titanium dioxide, 2-4 parts of the first antioxidant, 1-2 parts of plasticizer; The acrylic ester copolymer includes ethylene-ethyl acrylate copolymer and ethylene-methyl methacrylate copolymer; the weight ratio of the ethylene-ethyl acrylate copolymer to the ethylene-methyl methacrylate copolymer is 3:17-17:3.
[0005] As a further technical solution, the weight ratio of the ethylene-ethyl acrylate copolymer to the ethylene-methyl methacrylate copolymer is 2-3:1.
[0006] When the weight ratio of ethylene-ethyl acrylate copolymer to ethylene-methyl methacrylate copolymer is 2~3:1, the mechanical properties and aging resistance of wires and cables can be further improved.
[0007] As a further technical solution, the titanium dioxide is modified titanium dioxide, and the raw materials of the modified titanium dioxide include titanium dioxide and ternary polycarboxylic acid.
[0008] Surface modification of titanium dioxide using ternary polycarboxylic acid helps to evenly disperse titanium dioxide in the protective layer and can also strengthen the binding effect with acrylic copolymers, thereby further improving the mechanical properties of wires and cables.
[0009] As a further technical solution, the weight ratio of the titanium dioxide to the ternary polycarboxylic acid is 9-14:1.
[0010] When the weight ratio of titanium dioxide to ternary polycarboxylic acid is 9~14:1, the mechanical properties of wires and cables can be further improved.
[0011] As a further technical solution, the preparation method of the modified titanium dioxide comprises the following steps: dissolving the ternary polycarboxylic acid in anhydrous ethanol to obtain a ternary polycarboxylic acid solution, adding the titanium dioxide to the ternary polycarboxylic acid solution, dispersing evenly, concentrating, and drying to obtain the modified titanium dioxide.
[0012] As a further technical solution, the raw material of the modified titanium dioxide also includes nano-sized aluminum-magnesium hydrotalcite, and the weight ratio of the titanium dioxide, nano-sized aluminum-magnesium hydrotalcite and ternary polycarboxylic acid is 7-27:2:1.
[0013] In the process of modifying titanium dioxide, nano-aluminum-magnesium hydrotalcite is added. The surface of titanium dioxide is modified by nano-aluminum-magnesium hydrotalcite and ternary polycarboxylic acid, which can further improve the mechanical properties of wires and cables. It is speculated that the co-existence of nano-aluminum-magnesium hydrotalcite and ternary polycarboxylic acid can promote the titanium dioxide to be more uniformly present in the protective layer, and make the components of the protective layer more closely combined, thereby further improving the mechanical properties of wires and cables. In addition, when the weight ratio of titanium dioxide, nano-aluminum-magnesium hydrotalcite and ternary polycarboxylic acid is 7~27:2:1, the mechanical properties of wires and cables can be further improved.
[0014] As a further technical solution, the mass fraction of the ternary polycarboxylic acid solution is 5% to 10%.
[0015] As a further technical solution, the preparation method of the modified titanium dioxide comprises the following steps: A1, blending the titanium dioxide and the nano-scale aluminum-magnesium hydrotalcite, grinding, to obtain a mixture; A2. Dissolving the ternary polycarboxylic acid in anhydrous ethanol to obtain the ternary polycarboxylic acid solution, adding the mixture to the ternary polycarboxylic acid solution, dispersing evenly, concentrating, and drying to obtain the modified titanium dioxide.
[0016] As a further technical solution, the particle size of the titanium dioxide is 60-80 μm, and the particle size of the nano-scale aluminum-magnesium hydrotalcite is 50-80 nm.
[0017] As a further technical solution, the mass fraction of the ternary polycarboxylic acid solution is 5% to 10%.
[0018] As a further technical solution, the insulating layer comprises the following components in parts by weight: 50 parts of linear high-density polyethylene, 15-20 parts of chlorosulfonated polyethylene, 15-20 parts of EPDM rubber, and 1-3 parts of a second antioxidant.
[0019] As a further technical solution, the first antioxidant and the second antioxidant are independently one or both of antioxidant 1010 and antioxidant 168; the plasticizer is one or both of diisononyl phthalate and dioctyl adipate.
[0020] The present invention also provides a preparation process of an aging-resistant electric wire and cable, comprising the following steps: S1, blending and extruding the insulating layer components to obtain the insulating layer material; S2, blending and extruding the protective layer components to obtain the protective layer material; S3, coating the insulating layer material on the surface of the conductor to obtain a conductor containing an insulating layer; S4. Wrapping the protective layer material on the surface of the conductor containing the insulating layer to obtain the wire and cable.
[0021] As a further technical solution, in step S1, the temperature during extrusion is 150-170°C; in step S2, the temperature during extrusion is 160-180°C.
[0022] The working principle and beneficial effects of the present invention are: In the present invention, acrylic copolymers are added to the protective layer of the wire and cable, and the acrylic copolymers include ethylene-ethyl acrylate copolymer and ethylene-methyl methacrylate copolymer. Through the synergistic effect of two different types of acrylic copolymers, the components in the protective layer are helped to combine more closely, thereby effectively improving the mechanical properties and aging resistance of the wire and cable. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] In the following embodiments and comparative examples, the model of linear high-density polyethylene is HF7740F2; the model of ethylene-ethyl acrylate copolymer is AC2615; the model of ethylene-methyl methacrylate copolymer is ElvaloyAC-1224; the model of ternary polycarboxylic acid is SYS50; the model of chlorosulfonated polyethylene is LHYJ33; the model of ethylene propylene diene monomer rubber is EPDM 4770; the particle size of titanium dioxide is 75 μm; and the particle size of nano-aluminum-magnesium hydrotalcite is 80 nm.
[0025] Example 1 An aging-resistant wire and cable comprises a conductor, an insulating layer and a protective layer from the inside to the outside, wherein the protective layer comprises the following components in parts by weight: 70 parts of linear high-density polyethylene, 20 parts of acrylic copolymer, 15 parts of titanium dioxide, 2 parts of antioxidant 1010, 1 part of diisononyl phthalate; The acrylic copolymer includes 3 parts of ethylene-ethyl acrylate copolymer and 17 parts of ethylene-methyl methacrylate copolymer; The insulating layer includes the following components in parts by weight: 50 parts of linear high density polyethylene, 15 parts of chlorosulfonated polyethylene, 15 parts of EPDM rubber, 1 part of antioxidant 1010; The preparation process of the aging-resistant wire and cable comprises the following steps: S1, blending and extruding the insulating layer components to obtain an insulating layer material; S2, blending and extruding the protective layer components to obtain a protective layer material; S3, coating the insulating layer material on the surface of the conductor to obtain a conductor containing an insulating layer; S4, coating the protective layer material on the surface of the conductor containing the insulating layer to obtain the wire and cable; In step S1, during extrusion, the extrusion temperature of zone 1 is 150°C, the extrusion temperature of zone 2 is 170°C, and the extrusion temperature of zone 3 is 160°C; in step S2, the extrusion temperature of zone 1 is 160°C, the extrusion temperature of zone 2 is 180°C, and the extrusion temperature of zone 3 is 170°C.
[0026] Example 2 An aging-resistant wire and cable comprises a conductor, an insulating layer and a protective layer from the inside to the outside, wherein the protective layer comprises the following components in parts by weight: 70 parts of linear high-density polyethylene, 24 parts of acrylic copolymer, 30 parts of titanium dioxide, 3 parts of antioxidant 1010, 1.5 parts of diisononyl phthalate; The acrylic copolymer includes 14 parts of ethylene-ethyl acrylate copolymer and 10 parts of ethylene-methyl methacrylate copolymer; The insulating layer includes the following components in parts by weight: 50 parts of linear high density polyethylene, 18 parts of chlorosulfonated polyethylene, 18 parts of EPDM rubber, 2 parts of antioxidant 1010; The preparation process of the aging-resistant wire and cable comprises the following steps: S1, blending and extruding the insulating layer components to obtain an insulating layer material; S2, blending and extruding the protective layer components to obtain a protective layer material; S3, coating the insulating layer material on the surface of the conductor to obtain a conductor containing an insulating layer; S4, coating the protective layer material on the surface of the conductor containing the insulating layer to obtain the wire and cable; In step S1, during extrusion, the extrusion temperature of zone 1 is 150°C, the extrusion temperature of zone 2 is 170°C, and the extrusion temperature of zone 3 is 160°C; in step S2, the extrusion temperature of zone 1 is 160°C, the extrusion temperature of zone 2 is 180°C, and the extrusion temperature of zone 3 is 170°C.
[0027] Example 3 An aging-resistant wire and cable comprises a conductor, an insulating layer and a protective layer from the inside to the outside, wherein the protective layer comprises the following components in parts by weight: 70 parts of linear high density polyethylene, 30 parts of acrylic copolymer, 35 parts of titanium dioxide, 4 parts of antioxidant 1010, 2 parts of diisononyl phthalate; The acrylic copolymer includes 25.5 parts of ethylene-ethyl acrylate copolymer and 4.5 parts of ethylene-methyl methacrylate copolymer; The insulating layer includes the following components in parts by weight: 50 parts of linear high density polyethylene, 20 parts of chlorosulfonated polyethylene, 20 parts of EPDM rubber, 3 parts of antioxidant 1010; The preparation process of the aging-resistant wire and cable comprises the following steps: S1, blending and extruding the insulating layer components to obtain an insulating layer material; S2, blending and extruding the protective layer components to obtain a protective layer material; S3, coating the insulating layer material on the surface of the conductor to obtain a conductor containing an insulating layer; S4, coating the protective layer material on the surface of the conductor containing the insulating layer to obtain the wire and cable; In step S1, during extrusion, the extrusion temperature of zone 1 is 150°C, the extrusion temperature of zone 2 is 170°C, and the extrusion temperature of zone 3 is 160°C; in step S2, the extrusion temperature of zone 1 is 160°C, the extrusion temperature of zone 2 is 180°C, and the extrusion temperature of zone 3 is 170°C.
[0028] Example 4 The only difference between this embodiment and embodiment 2 is that in this embodiment, the acrylic ester copolymer includes 20 parts of ethylene-ethyl acrylate copolymer and 4 parts of ethylene-methyl methacrylate copolymer.
[0029] Example 5 The only difference between this embodiment and embodiment 2 is that in this embodiment, the acrylic ester copolymer includes 16 parts of ethylene-ethyl acrylate copolymer and 8 parts of ethylene-methyl methacrylate copolymer.
[0030] Example 6 The only difference between this embodiment and embodiment 2 is that in this embodiment, the acrylic ester copolymer includes 18 parts of ethylene-ethyl acrylate copolymer and 6 parts of ethylene-methyl methacrylate copolymer.
[0031] Example 7 The only difference between this embodiment and embodiment 6 is that in this embodiment, the titanium dioxide is modified titanium dioxide, and the preparation method of the modified titanium dioxide comprises the following steps: dissolving 4 parts of ternary polycarboxylic acid in anhydrous ethanol to obtain a ternary polycarboxylic acid solution with a mass fraction of 6%, adding 26 parts of titanium dioxide to the ternary polycarboxylic acid solution with a mass fraction of 6%, dispersing evenly, concentrating, and drying to obtain modified titanium dioxide.
[0032] Example 8 The only difference between this embodiment and embodiment 7 is that in this embodiment, 29 parts of titanium dioxide and 1 part of ternary polycarboxylic acid are added.
[0033] Example 9 The only difference between this embodiment and embodiment 7 is that in this embodiment, 27 parts of titanium dioxide and 3 parts of ternary polycarboxylic acid are added.
[0034] Example 10 The only difference between this embodiment and embodiment 7 is that in this embodiment, 28 parts of titanium dioxide and 2 parts of ternary polycarboxylic acid are added.
[0035] Embodiment 11 The difference between this embodiment and embodiment 10 is that, in this embodiment, the raw material of modified titanium dioxide further includes nano-grade aluminum-magnesium hydrotalcite, and the preparation method of modified titanium dioxide includes the following steps: A1. Blend 19.5 parts of titanium dioxide and 7 parts of nano-grade aluminum-magnesium hydrotalcite, grind, and obtain a mixture; A2. Dissolve 3.5 parts of ternary polycarboxylic acid in anhydrous ethanol to obtain a ternary polycarboxylic acid solution with a mass fraction of 6%. Add the mixture to the ternary polycarboxylic acid solution with a mass fraction of 6%, disperse evenly, concentrate, and dry to obtain modified titanium dioxide.
[0036] Example 12 The only difference between this embodiment and embodiment 11 is that in this embodiment, 28.5 parts of titanium dioxide, 1 part of nano-grade aluminum-magnesium hydrotalcite, and 0.5 part of ternary polycarboxylic acid are added.
[0037] Embodiment 13 The only difference between this embodiment and embodiment 11 is that in this embodiment, 21 parts of titanium dioxide, 6 parts of nano-grade aluminum-magnesium hydrotalcite, and 3 parts of ternary polycarboxylic acid are added.
[0038] Embodiment 14 The only difference between this embodiment and embodiment 11 is that in this embodiment, 27 parts of titanium dioxide, 2 parts of nano-grade aluminum-magnesium hydrotalcite and 1 part of ternary polycarboxylic acid are added.
[0039] Comparative Example 1 The difference between this comparative example and Example 1 is that in this comparative example, no ethylene-methyl methacrylate copolymer is added, and 20 parts of ethylene-ethyl acrylate copolymer is added.
[0040] Comparative Example 2 The difference between this comparative example and Example 1 is that in this comparative example, no ethylene-ethyl acrylate copolymer is added, and 20 parts of ethylene-methyl methacrylate copolymer is added.
[0041] Comparative Example 3 The only difference between this comparative example and Example 1 is that in this comparative example, no acrylic acid ester copolymer is added.
[0042] Experimental Example 1 Mechanical Properties The protective layer materials of the wires and cables prepared in Examples 1 to 14 and Comparative Examples 1 to 3 were tested for tensile strength according to the test method in GB / T 1040.1-2018 "Determination of tensile properties of plastics Part 1: General", wherein the test speed was 200 mm / min; The test results are shown in Table 1 below: Table 1 Test results
[0043] In Table 1, compared with Comparative Examples 1 to 3, the tensile strength of Example 1 is significantly improved, indicating that when the acrylic ester copolymer includes ethylene-ethyl acrylate copolymer and ethylene-methyl methacrylate copolymer, the ethylene-ethyl acrylate copolymer and the ethylene-methyl methacrylate copolymer have a synergistic effect and can improve the mechanical properties of wires and cables.
[0044] Compared with Examples 2 and 4, the tensile strength of Examples 5 to 6 is improved, indicating that when the weight ratio of ethylene-ethyl acrylate copolymer to ethylene-methyl methacrylate copolymer is 2 to 3:1, the mechanical properties of wires and cables can be further improved.
[0045] Compared with Example 6, the tensile strength of Examples 7 to 10 is improved, indicating that the mechanical properties of wires and cables can be further improved by surface modification of titanium dioxide using ternary polycarboxylic acid. In addition, compared with Examples 7 to 8, the tensile strength of Examples 9 to 10 is improved, indicating that when the weight ratio of titanium dioxide to ternary polycarboxylic acid is 9 to 14:1, the mechanical properties of wires and cables can be further improved. Compared with Example 10, the tensile strength of Examples 11 to 14 is improved, indicating that the mechanical properties of wires and cables can be further improved by surface modification of titanium dioxide by nano-aluminum-magnesium hydrotalcite and ternary polycarboxylic acid. In addition, compared with Examples 11 to 12, the tensile strength of Examples 13 to 14 is improved, indicating that when the weight ratio of titanium dioxide, nano-aluminum-magnesium hydrotalcite and ternary polycarboxylic acid is 7 to 27:2:1, the mechanical properties of wires and cables can be further improved.
[0046] Experimental Example 2 Aging resistance After the protective layer materials of the wires and cables prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were subjected to an aging resistance test according to the method in GB / T 7141-2008 "Test Methods for Thermal Aging of Plastics", the tensile strength test after the aging resistance test was carried out according to the above-mentioned tensile strength test method, and the aging resistance tensile strength retention rate was calculated according to the following formula: aging resistance tensile strength retention rate = tensile strength after aging resistance test / tensile strength before aging resistance test × 100%; wherein, when conducting the aging resistance test, the ventilation rate was 50 times / h, the experimental temperature was 100°C, and the exposure time was 96h; The test results are shown in Table 2 below: Table 2 Test results
[0047] In Table 2, compared with Comparative Examples 1 to 3, the aging resistance tensile strength retention rate of Example 1 is significantly improved, indicating that when the acrylic ester copolymer includes ethylene-ethyl acrylate copolymer and ethylene-methyl methacrylate copolymer, the ethylene-ethyl acrylate copolymer and the ethylene-methyl methacrylate copolymer have a synergistic effect and can improve the aging resistance of wires and cables.
[0048] Compared with Examples 2 and 4, the aging resistance tensile strength retention rate of Examples 5 to 6 is improved, indicating that when the weight ratio of ethylene-ethyl acrylate copolymer to ethylene-methyl methacrylate copolymer is 2 to 3:1, the aging resistance of wires and cables can be further improved.
[0049] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An aging-resistant wire and cable, comprising a conductor, an insulating layer and a protective layer from the inside to the outside, characterized in that: The protective layer includes the following components in parts by weight: 70 parts of linear high-density polyethylene, 20-30 parts of acrylic copolymer, 15-35 parts of titanium dioxide, 2-4 parts of the first antioxidant, 1-2 parts of plasticizer; The acrylic ester copolymer includes ethylene-ethyl acrylate copolymer and ethylene-methyl methacrylate copolymer; the weight ratio of the ethylene-ethyl acrylate copolymer to the ethylene-methyl methacrylate copolymer is 3:17-17:
3.
2. The aging-resistant wire and cable according to claim 1, characterized in that: The weight ratio of the ethylene-ethyl acrylate copolymer to the ethylene-methyl methacrylate copolymer is 2-3:
1.
3. The aging-resistant wire and cable according to claim 1, characterized in that: The titanium dioxide is modified titanium dioxide, and the raw materials of the modified titanium dioxide include titanium dioxide and ternary polycarboxylic acid.
4. The aging-resistant wire and cable according to claim 3, characterized in that: The weight ratio of the titanium dioxide to the ternary polycarboxylic acid is 9-14:
1.
5. The aging-resistant wire and cable according to claim 3, characterized in that: The preparation method of the modified titanium dioxide comprises the following steps: dissolving the ternary polycarboxylic acid in anhydrous ethanol to obtain a ternary polycarboxylic acid solution, adding the titanium dioxide into the ternary polycarboxylic acid solution, dispersing uniformly, concentrating, and drying to obtain the modified titanium dioxide.
6. The aging-resistant wire and cable according to claim 3, characterized in that: The raw materials of the modified titanium dioxide also include nano-sized aluminum-magnesium hydrotalcite, and the weight ratio of the titanium dioxide, nano-sized aluminum-magnesium hydrotalcite and ternary polycarboxylic acid is 7-27:2:
1.
7. The aging-resistant wire and cable according to claim 6, characterized in that: The preparation method of the modified titanium dioxide comprises the following steps: A1, blending the titanium dioxide and the nano-scale aluminum-magnesium hydrotalcite, grinding, to obtain a mixture; A2. Dissolving the ternary polycarboxylic acid in anhydrous ethanol to obtain the ternary polycarboxylic acid solution, adding the mixture to the ternary polycarboxylic acid solution, dispersing evenly, concentrating, and drying to obtain the modified titanium dioxide.
8. The aging-resistant wire and cable according to claim 1, characterized in that: The insulating layer comprises the following components in parts by weight: 50 parts of linear high-density polyethylene, 15-20 parts of chlorosulfonated polyethylene, 15-20 parts of EPDM rubber, and 1-3 parts of a second antioxidant.
9. The aging-resistant wire and cable according to claim 8, characterized in that: The first antioxidant and the second antioxidant are independently one or both of antioxidant 1010 and antioxidant 168; the plasticizer is one or both of diisononyl phthalate and dioctyl adipate.
10. A process for preparing an aging-resistant electric wire and cable according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, blending and extruding the insulating layer components to obtain the insulating layer material; S2, blending and extruding the protective layer components to obtain the protective layer material; S3, coating the insulating layer material on the surface of the conductor to obtain a conductor containing an insulating layer; S4. Wrapping the protective layer material on the surface of the conductor containing the insulating layer to obtain the wire and cable.
Citation Information
Cited By
High-strength polyethylene water supply pipe and preparation method thereof
CN121554847A
High-strength polyethylene water supply pipe and method for manufacturing the same
CN121554847B
